Multifocal osteonecrosis secondary to occupational exposure to aluminum - Jorge Henrique Assunção; Eduardo Angeli Malavolta; Mauro Emilio Conforto Gracitelli; Renée Zon Filippi; Arnaldo Amado Ferreira Neto (Acta Ortopédica Brasileira, 2017)
ABSTRACT Multifocal osteonecrosis is a rare disease; chronic use of corticosteroids is considered the main risk factor. Patients with chronic renal failure can develop aluminum toxicity, which can lead to osteomalacia and encephalopathy. An association between osteonecrosis and aluminum toxicity has been reported among patients with dialytic renal insufficiency. Occupational exposure to aluminum rarely causes lung disease and no cases of bone lesions resulting from exposure to this metal have been reported. In this manuscript, we describe a novel case of a patient with multifocal osteonecrosis associated with chronic occupational exposure to aluminum. Level of Evidence IV, Case Report.